Nuclear ARRB1 induces pseudohypoxia and cellular metabolism reprogramming in prostate cancer. (16th May 2014) - Zecchini, Vincent; Madhu, Basetti; Russell, Roslin; Pértega‐Gomes, Nelma; Warren, Anne; Gaude, Edoardo; Borlido, Joana; Stark, Rory; Ireland‐Zecchini, Heather; Rao, Roheet; Scott, Helen; Boren, Joan; et al.
<x xml:space="preserve">Abstract</x> Global chromatin occupancy‐ and gene expression data, together with 'pseudohypoxic' regulation of HIF1alpha stability establish a predominantly metabolic function of nuclear ARRB1 in prostate cancer. <boxed-text content-type="graphic" id="embj201386874-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>